Digital literacy and online course design: Study of Indonesian educators - Stefany, Stella; Helmi, Jessica (LPMPP Universitas Negeri Yogyakarta, 2024)
This paper explores the role of the digital literacy of Indonesian educators in their competence regarding online course design, in a Distance Education context, at tertiary level. It focuses on the competence of lecturers regarding digital literacy, and self-perceived ability in designing online courses. Lecturers (n = 275) at both public and private universities in Indonesia participated in this study. The developed instrument, measuring seven elements of digital literacy competence, in a teaching and pedagogical framework (Payton and Hague 2010), and six components of effective course design, aimed at achieving desired learning outcomes for students, was adopted from that of Brown and Voltz (2005). The result of Pearson's correlation testing indicated a strong relationship between two variables r (275) = .765, p < .001. The findings also showed that the digital literacy competence of educators had an influence of 58.6% on the quality of online course design, with a significant impact (F(1)=386.358; p=.000). It may therefore be concluded that it is important to upscale the digital literacy competence of lecturers, to promote the quality of online course design, in order to achieve desired learning outcomes. Further studies should particularly consider measuring the impact of online course design on the quality assurance of the course.